UMP hosts 49th Public University Golf Tournament - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 28 May 2022 - A Perodua ATIVA sponsored by Perusahaan Otomobil Kedua Sdn. Bhd. (PERODUA) for Hole In One became the players’ aim at the 49th Public University Golf Tournament which saw Universiti Malaysia Pahang (UMP) as the host.